2023
DOI: 10.3389/fonc.2023.1049294
|View full text |Cite
|
Sign up to set email alerts
|

Application of enhanced recovery after surgery in partial nephrectomy for renal tumors: A systematic review and meta-analysis

Abstract: ObjectivesIn recent years, enhanced recovery after surgery (ERAS) has been widely used in the field of urology, especially in radical cystectomy and radical prostatectomy, and has demonstrated its advantages. Although studies on the application of ERAS in partial nephrectomy for renal tumors are increasing, the conclusions are mixed, especially in terms of postoperative complications, etc, and its safety and efficacy are questionable. We conducted a systematic review and meta-analysis to assess the safety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…LOS is a crucial indicator for measuring the effectiveness of integrated care ERAS protocols. In this study, either pooled or subgroup analyses strongly suggested that ERAS management after ESS could reduce the LOS of CRS patients effectively, which is congruous with the reported findings from other meta-analysis research on ERAS protocols including bariatric surgery by Zhou et al [15], cesarean section by Meng et al [11], renal tumor resection by Wu et al [50], and pancreaticoduodenectomy by Cao et al [51]. The above-mentioned research demonstrates that patients receiving ERAS mode could often be discharged from the hospital earlier than that receiving conventional care.…”
Section: Discussionsupporting
confidence: 84%
“…LOS is a crucial indicator for measuring the effectiveness of integrated care ERAS protocols. In this study, either pooled or subgroup analyses strongly suggested that ERAS management after ESS could reduce the LOS of CRS patients effectively, which is congruous with the reported findings from other meta-analysis research on ERAS protocols including bariatric surgery by Zhou et al [15], cesarean section by Meng et al [11], renal tumor resection by Wu et al [50], and pancreaticoduodenectomy by Cao et al [51]. The above-mentioned research demonstrates that patients receiving ERAS mode could often be discharged from the hospital earlier than that receiving conventional care.…”
Section: Discussionsupporting
confidence: 84%
“…Studies on preoperative information which can identify patients at increased risk of postoperative complications are warranted. Also, improving preoperative optimization and postoperative rehabilitation could possibly further increase the benefits of surgery [ 36 ]. Finally, there is little information available on patient-related outcomes, such as patient choice and quality of life after cancer treatment, in elderly patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether less traumatic methods, such as RAPN, could increase the bene ts of surgery remains unknown. Also, improving preoperative optimization and postoperative rehabilitation could possibly further increase the bene ts of surgery [35]. Finally, there is little information available on patient-related outcomes, such as patient choice and quality of life after cancer treatment, in elderly patients [14].…”
Section: Discussionmentioning
confidence: 99%